Did the New Italian Law on Mandatory Vaccines Affect Adverse Event Following Immunization’s Reporting? A Pharmacovigilance Study in Southern Italy - Scavone, Cristina; Rafaniello, Concetta; Brusco, Simona; Bertini, Michele; Menditto, Enrica; Orlando, Valentina; Trama, Ugo; Sportiello, Liberata; Rossi, Francesco; Capuano, Annalisa (Frontiers in Pharmacology, 2018)
Despite the well-recognized role of vaccines, coverage is far from optimal especially in children, representing a growing concern also in Italy. In order to reverse this emergency, the Italian Ministry approved in July 2017 the Law 119/2017, which renders mandatory and free of charge ten vaccinations for patients aged 0-16. We aim to investigate the effects of the new Law 119/2017 on the reporting of adverse events following immunization related to mandatory vaccines into the Italian Pharmacovigilance database (Rete Nazionale di Farmacovigilanza - RNF). Therefore, we analyzed the spontaneous reports of suspected adverse events following immunization recorded in Campania Region (South of Italy) from December 1st 2016 to March 31st 2018. During the study period, 69 reports, covering 179 AEFIs, related to mandatory vaccines were sent to Campania Pharmacovigilance Regional Centre. A substantial increase in AEFIs reporting was observed after the adoption of Law 119/2017. Out of 69 reports, 62% reported AEFIs that were considered as not serious and 78% had a favorable outcome. Out of 179 AEFIs, more than half referred to the following SOC: “general disorders and administration site conditions”, “nervous system disorders”, and “psychiatric disorders”. The highest number of reports came from patient/citizen. After the adoption of the Law 119/2017, there was an increase in the number of reports (18 before the adoption of the Law vs. 51 after).According to reported AEFIs during the entire period, no worrying safety data have emerged. In our opinion, the increase in the number of AEFIs’ reports should be related to the increase in vaccination coverage as well as to the intense debate that has followed the new Law. In this context, the continuous monitoring of vaccine safety and the fully implementation of vaccine-vigilance programs play a key role in achieving higher confidence in immunization programs and optimal vaccination coverage rate.